PENGARUH PEMBERIAN SARI KACANG HIJAU (Vigna Radiata) TERHADAP KADAR HEMOGLOBIN IBU HAMIL ANEMIA - Vina Aulia; Sunarto Sunarto; Arintina Rahayuni (Poltekkes Kemenkes Semarang, 2018)
Background : Based on the results of Basic Health Research (Riskesdas) in 2013, the prevalence of anemia in pregnant women in Indonesia is 37,1%. The incidence of anemia in Central Java in 2015 reached 56,2% which is higher than the national rate of 50,5%. The incidence of anemia in pregnant women will increase the risk of maternal death. To reduce the incidence of anemia in pregnant women is done by consuming at least 90 Fe tablets, but must be supported and assisted by providing intake of foods rich in iron. One type of peanuts that contain high in iron is mungbean. Mungbean contain the substances needed for the formation of blood cells that can overcome the effects of decreased hemoglobin.Objective : To know the effect of mungbeans juice on hemoglobin levels of anemia pregnant women.Method : This study used the Pretest-Posttest Control GroupDesign. Number of samples each group of 10 people interventions performed on the treatment group in the form of mungbeans juice for 20 days in anemia pregnant women who consumed Fe tablets while control group only consumed Fe tablets. Test used to know the effect of intervention on hemoglobin level using ANOVA Repeated Measure with α = 0,05.Result : The mean elevation of hemoglobin level after intervention in the treatment group was 0,84 g/dl and in the control group 0,71 g/dl. Based on the results of anova test, there was no significant effect (p=0,452) of mungbeans juice on hemoglobin levels of anemia pregnant women after controlled with energy, protein, iron, vitamin C and vitamin A intake.Conclusion : There was no significant effect of mungbean juice on hemoglobin levels of anemia pregnant women.